Bites and Bytes: Exploring Customer Experience and Satisfaction in Food Delivery Services: A Case Study of Foodpanda - Chen, YiWen; Mui Hung Kee, Daisy; Dong, ShanShan; Wang, Zhuo; Zhu, JunChen (The Global Academia Publisher, 2025)
Foodpanda, one of the popular food delivery platforms, offers customers a fast and convenient way to order meals from local restaurants directly to their homes. Our study examines key factors influencing customer experience and satisfaction with Foodpanda, with specific objectives to (1) assess the impact of perceived usefulness, ease of use, trust, risk, and convenience on customer experience; (2) evaluate how these factors influence customer satisfaction; and (3) analyze the relationship between customer experience and satisfaction in the context of Foodpanda’s services. Data was collected from 154 customers. Our findings show that perceived ease of use, perceived trust, and perceived convenience have a significant positive impact on customer experience, while perceived convenience and perceived ease of use also play a role in shaping customer satisfaction. Our study reveals a strong positive relationship between customer experience and customer satisfaction, demonstrating that enhancing customer experience leads to improved satisfaction levels. These findings highlight the critical importance of ease of use, trust, and convenience in influencing both customer experience and satisfaction within the food delivery industry